Frequency of Bronchestasis among Post Tuberculosis Patients in Mti-Mardan Medical Complex Mardan - Hussain, Zahid; Ali, Sajjad; Bilal, Sabir; Hidayat Ullah (Indus Journal of Bioscience Research, 2025)
Background: Bronchiectasis has emerged as an established long-term sequelae of pulmonary tuberculosis with resultant chronic respiratory symptoms and quality-of-life impairment. It is vital to establish its prevalence and risk factors since it occurs in areas where tuberculosis is common and where healthcare facilities are scarce. Objective: To find out the frequency of bronchiectasis among post-tuberculosis patients. Study Design: Descriptive cross-sectional study. Duration and Place of Study: The study was conducted from February to May 2025 at the Department of Pulmonology, MTI-Mardan Medical Complex, Mardan. Methodology: A total of 137 patients aged 18–70 years with a documented history of pulmonary tuberculosis were enrolled using WHO sample size calculation. Diagnosis of history of tuberculosis was confirmed on the basis of sputum culture and by clinical criteria. Exclusion criteria included asthma, COPD, chronic kidney disease, and pregnancy. Chest radiography diagnosed bronchiectasis on the basis of characteristic radiological evidence confirmed by clinical symptomatology. Results: The mean age of patients was 47.44 ± 10.81 years, with nearly equal gender distribution. Overall, bronchiectasis was detected in 28 patients (20.4%). A significant association was observed between bronchiectasis and smoking status (p=0.001). Conclusion: Bronchiectasis is a relatively frequent complication in post-tuberculosis patients.